PENGARUH GAYA KEPEMIMPINAN,MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT.LOTTE SHOPPING INDONESIA - Alex Riyadi Putra; Riki (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2022)
This study aims to determine or test and analyze the influence of leadership style, motivation and work discipline on the performance of employees of PT. Lotte Shopping Indonesi in Batam. Data collection was carried out by distributing questionnaires and with a total of 70 respondents, data analysis used the IBM statistical version of the SPSS program 23. In this study, no sampling technique was used because the sample studied was the entire population, testing data used in this study included validity test, reliability test, classical assumption test and multiple linear regression analysis, to test and prove the research hypothesis.The results of the analysis in the f-table test show that the hypothesis in this study accepts H4 and rejects H0. So this states that Leadership Style (X1), Motivation (X2) and Employee Performance (X3) have a positive and significant effect on employee performance (Y).